Results of carotid artery stenting with distal embolic protection with improved systems: Protected Carotid Artery Stenting in Patients at High Risk for Carotid Endarterectomy (PROTECT) trial - Matsumura, Jon S.; Gray, William; Chaturvedi, Seemant; Yamanouchi, Dai; Peng, Lei; Verta, Patrick (Journal of vascular surgery, 2012)
The Protected Carotid Artery Stenting in Patients at High Risk for Carotid Endarterectomy (PROTECT) study was performed to evaluate the safety and effectiveness of two devices for carotid artery stenting (CAS) in the treatment of carotid artery stenosis in patients at high risk for carotid endarterectomy (CEA): (1) a new embolic protection device, the Emboshield Pro (Abbott Vascular, Abbott Park, Ill), using the periprocedural composite end point of 30-day death, stroke, and myocardial infarction (DSMI), and (2) a carotid stent in conjunction with an embolic protection device (EPD) using the DSMI periprocedural composite end point plus ipsilateral stroke at up to 3 years for long-term evaluation. This prospective, multicenter clinical trial enrolled 220 consecutive participants between November 29, 2006, and January 14, 2008, followed by a second cohort of 102 participants between January 14 and June 18, 2008. Enrolled participants had carotid stenosis (symptomatic >50% or asymptomatic >80%). The first 220 subjects underwent distal EPD placement with a new large-diameter filter, and the second cohort of 102 underwent placement of an older EPD that is no longer manufactured. All 322 participants were to be treated with a dedicated carotid stent with a tapered, small, closed-cell design (Xact; Abbott Vascular) and were to be included in the long-term evaluation. Independent neurologic assessment was performed before CAS and at 1 day, 30 days, and annually after CAS. All primary end point events were independently adjudicated by a central committee. The periprocedural composite end point of DSMI (95% confidence interval) in the first 220 participants was 2.3% (0.74%, 5.22%), with a combined death and stroke rate of 1.8% (0.50%, 4.59%) and a rate of death and major stroke of 0.5% (0.01%, 2.51%). As of January 3, 2011, the median follow-up for the entire 322-subject cohort for the long-term evaluation was 2.8 years. Freedom from the periprocedural composite of DSMI plus ipsilateral stroke thereafter was 95.4%, with an annualized ipsilateral stroke rate of 0.4%. CAS outcomes in patients at high risk for CEA have improved from earlier carotid stent trials. With periprocedural rates of DSMI of 2.3%, death or stroke at 1.8%, and death or major stroke rate of 0.5%, PROTECT has the lowest rate of periprocedural complications among other comparable single-arm CAS trials in patients at high risk for CEA.